2019
DOI: 10.1186/s13017-019-0251-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary resection anastomosis versus Hartmann’s procedure in Hinchey III and IV diverticulitis

Abstract: Introduction Surgical management of Hinchey III and IV diverticulitis utilizes either Hartmann’s procedure (HP) or primary resection anastomosis (PRA) with or without fecal diversion. The aim of this meta-analysis is to determine which of the two procedures has a more favorable outcome. Methods A systematic review of the existing literature was performed using the PRISMA guidelines. A meta-analysis was carried out using a Mantel-Haenszel, random effects model, and fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 41 publications
1
18
0
3
Order By: Relevance
“…Diverticular disease is a common gastrointestinal disease and found in one third of people over 60 in the Western world 4 . One of its main complications is diverticulitis, and it can be classified as uncomplicated (Hinchey classification I and II), and complicated (Hinchey classification III and IV) 9 . About 25% of patients with acute diverticulitis require emergency intervention, and the standardized treatment for the perforated form with fecal or purulent peritonitis (Hinchey III and IV classification) is emergency surgery 4 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Diverticular disease is a common gastrointestinal disease and found in one third of people over 60 in the Western world 4 . One of its main complications is diverticulitis, and it can be classified as uncomplicated (Hinchey classification I and II), and complicated (Hinchey classification III and IV) 9 . About 25% of patients with acute diverticulitis require emergency intervention, and the standardized treatment for the perforated form with fecal or purulent peritonitis (Hinchey III and IV classification) is emergency surgery 4 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…And hospital stay in the Hartmann group was less than primary anastomosis group in the same admission. Halim et al [ 30 ] analyzed the surgical outcomes from primary anastomosis and Hartmann's procedure and reported that mortality in primary anastomosis group was 40% lower than Hartmann's group. Similarly, a study by Sozen et al [ 31 ] concluded that Hartmann's procedure was associated with increased duration of hospitalization and need of reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the mid-2000s, there have been many discussions on the proper surgical management for colonic diverticular perforation, but there is still controversy [25]. In a systematic review and meta-analysis by Halim et al [7], 22 of 25 articles reported that PA was associated with lower in-hospital mortality than HP, however, the other 3 articles did not report this finding. Statistically, PA had lower in-hospital mortality than HP.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have reported that primary repair (PR) or primary anastomosis (PA) can improve levels of morbidity and mortality compared with HP. However, other studies have reported that PR or PA had no beneficial effect on mortality and morbidity [7].…”
Section: Introductionmentioning
confidence: 88%